Knowledge, renewal and flexibility: Exploratory research in family firms - Marta Pérez-Pérez; María Concepción López-Férnandez; María Obeso (Administrative Sciences, 2019)
This study aims to explore how family firms pursue strategies that promote strategic flexibility and knowledge-management (KM) practices to respond to strategic-renewal goals. Specifically, based on a knowledge-based view of the firm, the following research question is proposed: Are there heterogeneous groups of family firms in terms of knowledge management, strategic flexibility and strategic renewal goals? To answer this question, an exploratory study using a two-step cluster analysis is developed. It reveals natural groupings from a sample of 288 small and medium-sized Spanish family enterprises (SMEs). The results obtained identified three distinctive clusters of family firms, namely proactive family firms, transitional or adaptive family firms, and rigid family firms. After two-step cluster analysis, we also conducted analysis of variance (ANOVA) to confirm that significant differences amongst the three clusters exist. After heterogeneity been confirmed, a further profile of the cluster solution was provided by using CEO and board characteristics, as well as the generational stage of the company. The findings offer some counterbalance for those studies that tend to study family businesses as a homogeneous entity, thus permitting researchers to access more information, providing rich explanations for renewal managerial decision-making purposes in family firm contexts.
Keywords: 350; entrepreneurship; family firm; knowledge; flexibility; strategic renewal